PERANCANGAN PROTOTYPE SISTEM INFORMASI PROMOSI ASLAMIYAH FOODS DESA SENGKATI BARU KECAMATAN MERSAM: Design, Prototype, Information System, Promotion, Products - Anzari, Yandi; -, Mutmainnah (LP2M Universitas Nurdin Hamzah, 2025)
The rapid development of technology today has opened up opportunities for business people to utilize digital-based information systems in increasing product promotion. Aslamiyah Foods is a business that produces processed oyster mushrooms located in Sengkati Baru Village, Mersam District. Aslamiyah Foods faces obstacles in promoting its superior product, namely Aslamiyah Krenyesss Mushrooms. The promotion carried out so far is only by leaving products to several mini markets, participating in exhibitions held by the Batang Hari district government, as well as through whatsapp and instagram social media, but has not yet obtained optimal results. System modeling in this study uses the Unified Modeling Language (UML) including use case diagrams, activity diagrams, and class diagrams as well as the Prototype method which will be used in the process of designing promotional information systems. The results of this study are in the form of a Promotion Information System Dessign at Aslamiyah Foods, Sengkati Baru Village, Mersam District.